Testing software and systems : 31st IFIP WG 6.1 International Conference, ICTSS 2019, Paris, France, October 15-17, 2019, Proceedings /: 31st IFIP WG 6.1 International Conference, ICTSS 2019, Paris, France, October 15-17, 2019, Proceedings. (2019) - Unknown
No abstract available